EFFECTS OF SINTERING CONDITIONS OF SINTERED NI-ZN FERRITES ON PROPERTIES OF ELECTROMAGNETIC-WAVE ABSORBER - KIM, WS; YOON, SJ; KIM, KY (ELSEVIER SCIENCE BV, 1994)
The effects of sintering conditions of Ni-Zn ferrites on magnetic losses, magnetic properties, and behavior of electromagnetic wave adsorbers were investigated. A sintered Ni-Zn ferrite was obtained by sintering at 1250-degrees-C for 2 h with a heating rate of 12-degrees-C/min and a cooling rate of 2-degrees-C/min. It satisfied the absorbing properties of attenuation above 20 dB in the entire VHF and UHF bands for 6 mm thick electromagnetic wave adsorbers.